THE SPECIFITY OF BOOK SCIENCE IN EASTERN EUROPE AND FORMATION OF NATIONAL RESEARCH SCHOOLS TILL WORLD WAR II - MIGOÑ, KRZYSZTOF (Knygotyra, 2015)
The appearance of book science as an autonomous discipline of science can be traced back in Eastern Europe to the beginnings of the 19th century. It was evolving from bibliography, history of literature, editorial, bookselling and library activities and practice, and from educational needs. Its further growth has been enhanced by the rapid increase of book world, institutional and professional developments in book culture, and realization of a multitude of benefits arising from bibliological studies. The latter could have been identified in the field of science, development of ideas, social and political relations. Initially, theoretical background of East European bibliology was influenced by Western European concepts, particularly French and German. Afterwards, however, original concepts and specific approaches to book science have been developed in Poland, Russia, and Ukraine, followed by other countries. There has been a significant degree of unification observed in views and thoughts about book and book science, resultant from the largely common past of book culture in Eastern Europe, shared historical experience, political, language and religious situation, and fairly continuous exchange of scientific ideas. Nevertheless, local circumstances related to dissimilar traditions in book studies, variable influence of ideology and politics, uneven potential of scientific communities, and uneven recognition of the discipline in different countries, have left their clear imprint too. Their result is the variety of research paradigms, different focus points in book studies, and the development of various research schools, some of them specific for certain countries. The notion of ‘national research schools’, present in the science about science, was introduced by Robert Estivals, who wrote in the encyclopaedia Les sciences de l’écrit (1993): “The French school of bibliology is undoubtedly one the most important schools, besides the Belgian, Polish, Russian, and Swiss one. They are so much unlike the Anglo-saxon school, which tends to brings bibliography and bibliology together, that one may speak about the continental European bibliological school, different from English and North American concepts”. The essence of a national research school usually shows through a larger number of variables considered, convincing facts and evidence, but it also involves a certain degree of subjectivity, so that proper explanation is only achieved after considering opinions and emotions as well. In addition, the perception of research schools varies depending on the observer, whether from inside, through the eyes of representatives or supporters, or from outside. In the former case, there is a trend towards emphasizing differences in fundamental views about a given discipline or research direction. Consequently, different criteria of school identification are used (e.g. narrower subjects, influential persons or institutions), and the number of schools appears to grow. In the latter, though, a trend towards generalization and synthesis at broader spatial and temporal scales prevails. Breakthrough events in the development of national research schools in Eastern Europe include the origin and re-establishment of independent states after the World War I (Lithuania, Latvia, Estonia, Poland, Czechoslovakia), and later the collapse of Soviet Union in 1991, when Baltic states, Byelorussia and Ukraine have become independent, and substantial political and social changes occurred in all countries formerly belonging to the communist block. The characteristic features of book science in Eastern European countries – before and later after the World War II – appear to include the following: 1. focus on the history and present-day of own national cultures as a part of a wider framework of bibliological studies; 2. intensive theoretical research on book as a means of communication and as a cultural factor; 3. construction of numerous theoretical and methodological models of bibliology; 4. extensive development of historical studies, focused on the history of book culture; 5. close links between bibliological studies and other disciplines; 6. application of bibliological theory and history in the shaping of ontemporary book system.